2014
DOI: 10.3233/ch-141902
|View full text |Cite
|
Sign up to set email alerts
|

Organotypical vascular model for characterization of radioprotective compounds: Studies on antioxidant 2,3-diaryl-substituted indole-based cyclooxygenase-2 inhibitors

Abstract: Radiotherapy of various cancers is closely associated with increased cardiovascular morbidity and mortality. Arachidonic acid metabolites are supposed to play a key role in radiation-induced vascular dysfunction. This study was designed to evaluate the effects of novel, antioxidative 2,3-diaryl-substituted indole-based selective cyclooxygenase-2 (COX-2) inhibitors (2,3-diaryl-indole coxibs) on radiation-induced formation of arachidonic acid metabolites via COX-2 and oxidant stress pathways in an organotypical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…However, with respect to the clinical situation the development and evaluation of novel drug candidates or new strategies is of urgent need. Our own investigations provided experimental evidence on 2,3-diaryl-substituted indole-based COX-2 inhibitors exerting at pharmacologically low concentration levels antioxidant activity, for instance by scavenging • OH and O 2 •− thus protecting low density lipoproteins from oxidative damage as well as demonstrating radioprotection on both cellular and organotypical vascular models [ 30 , 31 ]. From these data we deduced the hypothesis that antioxidant COX-2 inhibitors can be considered to act as a double-edged sword by intervening in the immediate and also delayed responses to ionizing radiation.…”
Section: Biochemical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…However, with respect to the clinical situation the development and evaluation of novel drug candidates or new strategies is of urgent need. Our own investigations provided experimental evidence on 2,3-diaryl-substituted indole-based COX-2 inhibitors exerting at pharmacologically low concentration levels antioxidant activity, for instance by scavenging • OH and O 2 •− thus protecting low density lipoproteins from oxidative damage as well as demonstrating radioprotection on both cellular and organotypical vascular models [ 30 , 31 ]. From these data we deduced the hypothesis that antioxidant COX-2 inhibitors can be considered to act as a double-edged sword by intervening in the immediate and also delayed responses to ionizing radiation.…”
Section: Biochemical Backgroundmentioning
confidence: 99%
“…We have performed radioprotection studies with the sulfonyl-containing 2,3-diaryl-substituted indole RIVAD018 and observed an effect both in cellular and organotypical vascular models [ 30 , 31 ]. The 2,3-diaryl-substituted indoles have been initially developed by Hu and Guo et al as potent COX-2 selective inhibitors [ 136 , 137 , 138 ].…”
Section: 23-diaryl-substituted Indoles As Promising Radioprotectomentioning
confidence: 99%
See 2 more Smart Citations
“…It is an NSAID that inhibits cyclooxygenase (COX), the enzyme responsible for conversion of arachidonic acid to prostaglandins. In particular, CLX belong to the class of Coxib, the non-steroidal anti-inflammatory drugs that, unlike most NSAIDs, are selective for inhibiting COX-2, the induced isoform of the two existing COX [5], which is almost absent in normal healthy tissues and cells but it increase during inflammation process, induced by various proinflammatory, catabolic and stress mediators such as cytokines and growth factors.…”
Section: Introductionmentioning
confidence: 99%